Fiscal discipline in the achievement of fiscal & debt sustainability and growth in the Bahamas - Branch, Sharon G. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Examines fiscal developments in the Bahamas, as it relates to economic growth and debt sustainability. Focuses on fiscal discipline and tis implications for economic growth and debt sustainability within the Bahamian economy.